Wide and fine alignment control and interface modification for high-performance thermally conductive graphite/copper composite. (15th June 2020) - Cao, Huaijie; Tan, Zhanqiu; Fan, Genlian; Guo, Qiang; Su, Yishi; Li, Zhiqiang; Xiong, Ding-Bang
Abstract: A controlled alignment of micro-/nano-fillers with anisotropic morphology and properties in a composite matrix will allow developing materials with tailored properties, but which still remains challenging. Here, alignment of graphite plates in Cu matrix was well controlled in a wide range with fine steps by elaborately designed morphologies of copper powders. Polarized Raman scattering demonstrated that a record-high orientation degree could be obtained as assisted by Cu micro-flakes. Furthermore, owing to the improvements on intrinsic thermal conductivity of graphite by hot-pressing and graphite/Cu interface wettability by using in-situ graphene as interlayer, high-performance thermally conductive (~600 W/mK) and light-weight (4.9 g/cm 3 ) graphite/graphene-interlayer/Cu matrix composites were successfully fabricated. Graphical abstract: Image 1